If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(4x + -3) + -1x = 5 Reorder the terms: 2(-3 + 4x) + -1x = 5 (-3 * 2 + 4x * 2) + -1x = 5 (-6 + 8x) + -1x = 5 Combine like terms: 8x + -1x = 7x -6 + 7x = 5 Solving -6 + 7x = 5 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '6' to each side of the equation. -6 + 6 + 7x = 5 + 6 Combine like terms: -6 + 6 = 0 0 + 7x = 5 + 6 7x = 5 + 6 Combine like terms: 5 + 6 = 11 7x = 11 Divide each side by '7'. x = 1.571428571 Simplifying x = 1.571428571
| 4r-23=-14+r | | 2-3(x+2)=5x-4 | | x^2-10x+43=5x-1 | | (6x)+5=(5x)-12 | | 45+24h=405 | | x^2+2x-7=-7x+3 | | 2x-8+2x-7=15 | | -0.6+(-0.3)= | | -4+(v-2)=-4(v-8)-8v | | 3x-5x+7=-21 | | 4(x-3)-1=3x | | 4n+2=6n+8 | | 7=-11+3(y+5) | | 3y=-5x+6 | | m^2+mn-6n^2=0 | | 3x+4xy-(4x-xy+xyz)= | | 19=-2p+23 | | 0=14x+28 | | 6(4-w)=2w | | 5x-3=3(x+6) | | 3/2=18÷x | | 6a-5b=1 | | X^2+3x-12+-6=0 | | 3x+4-9-4x=12 | | v=4/3*3.14*(21)3 | | 4x=2(48-4) | | h/6-1= | | x(4x-6)=(4x+7)(x-5) | | 5X1/14 | | 2x+x-24=90 | | X-1=4x-22 | | 4x=2(48-3) |